Measuring Problem Solving Skills of High School Students on Biology - Naintyn Novitasari; Murni Ramli; Maridi Maridi (Universitas Syiah Kuala, 2015)
This study aimed to describe the characteristics and feasibility of high school students problem solving skills assessment on Biology. This research is using Research Development model which refers to Borg Gall. Assessment developed are open-ended cases. Product validation conducted by subject matter and evaluation experts. Test involving 88 students from three different schools. Data from the field test were analyzed using the Quest program. Assessment components that have been developed includedskills to defining the problem, checking the problem, planning a solution, implementing the plan, and evaluate.The study shows that the assessment instrument has a validity that fit with the Rasch model and high reliability. The final result that 13 % items were easy, 41,7 % items were moderate, and 46,3 % items were categorized as difficult. Discriminationindex in each item have a minimal interpretation of